Nigerian pentecostal churches and their prosperity messages: A safeguard against poverty in Nigeria? 1980 – 2014 - Rotimi, Nkechi C.; Nwadialor, Kanayo L.; Ugwuja, Alex Amaechi (Mgbakoigba: Journal of African Studies, 2016)
One can argue that the growth of Pentecostalism in Nigeria owes a lot to the rising spate of poverty and squalor in the country. When individuals began to seek spiritual solutions for their physical problem, Pentecostal churches with their prosperity messages logically appeared as anchor point. Pentecostalism - a term which describes the set of Christians who believe so much in the help of the Holy Spirit for overcoming life challenges – both spiritually and physically readily became a bastion of hope for a vast number of Nigerians who have had to struggle for an existence in the ailing Nigerian economy. The nexus between the claims and testimonies of the adherents of these Pentecostal churches and the social conditions in Nigeria appear not to have fully caught the attention of social historians. Simply put, are prosperity messages by Nigerian Pentecostal Churches a safe guard against poverty? This study attempts to find answers to these questions. Information for the study was derived from primary sources and secondary sources. The historical research method which emphasizes thematic analysis of information was employed. The salience of the study is inherent in its modest contribution to this seemingly under - studied social aspect of Nigerian history.
free